Tracheostomy for COVID-19 Respiratory Failure: Multidisciplinary, Multicenter Data on Timing, Technique, and Outcomes. Issue 2 (August 2021) - Mahmood, Kamran; Cheng, George Z.; Van Nostrand, Keriann; Shojaee, Samira; Wayne, Max T.; Abbott, Matthew; Nettlow, Darrell; Parish, Alice; Green, Cynthia L.; Safi, Javeryah; Brenner, Michael J.; De Cardenas, Jose
Abstract : Objective: The aim of this study was to assess the outcomes of tracheostomy in patients with COVID-19 respiratory failure. Summary Background Data: Tracheostomy has an essential role in managing COVID-19 patients with respiratory failure who require prolonged mechanical ventilation. However, limited data are available on how tracheostomy affects COVID-19 outcomes, and uncertainty surrounding risk of infectious transmission has led to divergent recommendations and practices. Methods: It is a multicenter, retrospective study; data were collected on all tracheostomies performed in COVID-19 patients at 7 hospitals in 5 tertiary academic medical systems from February 1, 2020 to September 4, 2020. Result: Tracheotomy was performed in 118 patients with median time from intubation to tracheostomy of 22 days (Q1–Q3: 18–25). All tracheostomies were performed employing measures to minimize aerosol generation, 78.0% by percutaneous technique, and 95.8% at bedside in negative pressure rooms. Seventy-eight (66.1%) patients were weaned from the ventilator and 18 (15.3%) patients died from causes unrelated to tracheostomy. No major procedural complications occurred. Early tracheostomy (⩽14 days) was associated with decreased ventilator days; median ventilator days (Q1–Q3) among patients weaned from the ventilator in the early, middle and late groups were 21 (21–31), 34 (26.5–42), and 37 (32–41) days, respectively with P = 0.030. Compared to surgical tracheostomy, percutaneous technique was associated with faster weaning for patients weaned off the ventilator [median (Q1–Q3): 34 (29–39) vs 39 (34–51) days, P = 0.038]; decreased ventilator-associated pneumonia (58.7% vs 80.8%, P = 0.039); and among patients who were discharged, shorter intensive care unit duration [median (Q1–Q3): 33 (27–42) vs 47 (33–64) days, P = 0.009]; and shorter hospital length of stay [median (Q1–Q3): 46 (33–59) vs 59.5 (48–80) days, P = 0.001]. Conclusion: Early, percutaneous tracheostomy was associated with improved outcomes compared to surgical tracheostomy in a multi-institutional series of ventilated patients with COVID-19. Abstract : Supplemental Digital Content is available in the text